2015
DOI: 10.1016/j.stemcr.2015.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Common Origins of Osteoclasts, Macrophages, and Dendritic Cells in Human Hematopoiesis

Abstract: SummaryOsteoclasts (OCs) originate from the myeloid cell lineage, but the successive steps in their lineage commitment are ill-defined, especially in humans. To clarify OC origin, we sorted cell populations from pediatric bone marrow (BM) by flow cytometry and assessed their differentiation potential in vitro. Within the CD11b−CD34+c-KIT+ BM cell population, OC-differentiation potential was restricted to FLT3+ cells and enriched in an IL3 receptor (R)αhigh subset that constituted less than 0.5% of total BM. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 28 publications
5
52
0
Order By: Relevance
“…We found that the GMP population could give rise to OCs (supplemental Figure 1E). This result, together with our findings in humans, 15 supports the concept that the GMP population contains a progenitor with combined GR, MF, OC, and DC potential that lies upstream of the MODP. We further hypothesized that the MOP lies downstream of the MODP ( Figure 1A).…”
Section: Cell Surface Markers Of Modp and Mopsupporting
confidence: 89%
See 4 more Smart Citations
“…We found that the GMP population could give rise to OCs (supplemental Figure 1E). This result, together with our findings in humans, 15 supports the concept that the GMP population contains a progenitor with combined GR, MF, OC, and DC potential that lies upstream of the MODP. We further hypothesized that the MOP lies downstream of the MODP ( Figure 1A).…”
Section: Cell Surface Markers Of Modp and Mopsupporting
confidence: 89%
“…We recently described the human (h)MODP 15 and noted that its cell surface phenotype was similar to that of the hCDP that was described shortly before that 28 ( Figure 7H). Both progenitor populations are very rare, representing about 0.2% of total BM ( Figure 7I).…”
Section: Comparison Of Cdp and Mdp With Modp And Mop: Differentiationmentioning
confidence: 56%
See 3 more Smart Citations